PUSAT PELATIHAN ATLET TAEKWONDO DI KOTABARU - Pratama, Muhammad Ryan; Wastuty, Prima Widya; Nurfansyah, Nurfansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Training is all efforts that result in an increase in ability in sports matches, so the notion of training is a training process that aims to improve sports ability. Taekwondo itself is a modern martial art that is rooted in traditional South Korean martial arts. one of the sports that has developed rapidly in Indonesia, and has shown its good quality in Indonesia and abroad, namely taekwondo, taekwondo has become very popular because movements in taekwondo have more benefits than just exercising, namely to form self-perfection in terms of personal character that is more agile in protecting oneself, Especially in Kotabaru itself taekwondo is the most popular sport especially since the many achievements they have achieved in previous years have made this sport popular, therefore the Taekwondo Athlete training center in Kotabaru can make a training that has complete facilities and can improve the achievements of athletes. With the concept of connectivity A concept where indoor and outdoor spaces are connected/connected properly.